Exploring Teachers' Educational Philosophies: A Comparative Analysis Based on Geographic Classifications - Cabiles, Roldan C. (Future Science / FSH-PH Publications, 2024)
This qualitative phenomenological research explores the lived experiences of key informants through in-depth interviews and participant observation. The teacher-participants, who work in three geographical areas, were identified by the Department of Education (DepED) in the Schools Division Office of Albay. The study is grounded in the phenomenological concepts and principles of Husserl (1859-1938) and Heidegger (1889-1976), along with the Reflection-Action perspective of Freire (1921-1997), to capture the essence of their experiences. Due to the global health crisis caused by COVID-19, data collection utilized virtual platforms such as Facebook Messenger, Google Meet, Zoom, and phone calls, in addition to face-to-face interviews when possible. Health protocols mandated by the Inter-Agency Task Force (IATF), including mask-wearing, social distancing, and the use of hand sanitizer, were strictly followed to ensure safety. The findings indicate that teachers from rural, urban, and coastal areas reflect various educational philosophies such as essentialism, humanism/existentialism, pragmatism/progressivism, reconstructionism, constructivism, idealism, behaviorism, and perennialism. Some teacher-participants from rural and coastal areas also exhibit positivism, influenced by their expertise in mathematics and science. These educational philosophies enhance their coping mechanisms and teaching competencies to adjust to the local cultural realities.